2012
DOI: 10.1097/iop.0b013e31823d2125
|View full text |Cite
|
Sign up to set email alerts
|

Does Upper Lid Blepharoplasty Improve Contrast Sensitivity?

Abstract: Dermatochalasis is well known to cause visual field defects in many patients. Anecdotally, patients often report that their vision is brighter following upper eyelid blepharoplasty. The authors have demonstrated a significant increase in contrast sensitivity in patients who have undergone upper eyelid blepharoplasty surgery. This information may be of use in justifying blepharoplasty surgery in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…These results are also consistent with studies in which patients with dermatochalasis reported subjective improvement in contrast sensitivity-related symptoms, such as increased image brightness and comfort in reading and driving, after surgery. 4 , 5 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are also consistent with studies in which patients with dermatochalasis reported subjective improvement in contrast sensitivity-related symptoms, such as increased image brightness and comfort in reading and driving, after surgery. 4 , 5 …”
Section: Discussionmentioning
confidence: 99%
“…In addition to the lash effect, allowing more light to enter the eye by eliminating the hooding effect caused by the overhanging skin fold is another proposed mechanism. 4 , 5 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies mainly show clinically insignificant, but statistically relevant, corneal topographic alterations. Some reports 24 , 25 also indicate improved contrast sensitivity, with alterations only in the high-order aberrations. The CCT, an important value for corneal structure, was unchanged in these studies.…”
Section: Discussionmentioning
confidence: 96%
“…Alterations were highly apparent in the lateral portion of the eyebrow and occur bilaterally. Rogers et al 63 have documented significant improvement in contrast sensitivity in patients who have undergone upper eyelid blepharoplasty. The measurement technique used by the authors to document the change in eyebrow position, however, seems objective.…”
Section: Blepharoplastymentioning
confidence: 99%